A novel weighted hybrid clinical and electrocardiographic score to predict the origin of outflow tract ventricular arrhythmias: a multicenter study. (19th May 2022) - Falasconi, G; Penela, D; Carreno, JM; Soto-Iglesias, D; Jauregui, B; Viveros, D; Bellido, A; Scherer, C; Benito, B; Marti, J; Sabate, X; Matiello, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: To correctly predict the outflow tract ventricular arrhythmia (OTVA) site of origin (SOO) before the ablation is still a procedural major step, having important implications for correct patient counseling, ablation planning, and periprocedural complication evaluation. Although multiple ECG criteria have been proposed for predicting OTVA SOO, their accuracy and usefulness are still limited as recently (1). Purpose: The present study sought to prospectively evaluate the accuracy of a previously published Hybrid Score (HS) for prediction of OTVAs with LVOT origin. Besides, multiple ECG measurements of patients with V3 precordial transition (V3PT) OTVA were analyzed to identify potential variables useful to improve the accuracy of the HS (2). Methods: Consecutive patients (n=105) referred for OTVA ablation were prospectively enrolled from three referral centers. Vascular access and first-mapped ventricle were decided based on the previously published HS, which includes ECG (R/S precordial transition) and clinical information (age, hypertension, and gender). Surface ECGs during the OTVA were analyzed by two independent electrophysiologists to compare the discriminative performance of HS and previous published ECG-alone criteria, to assess their inter-observer variability and to identify potential variables useful to improve the proposed model. Results: Of the 105 VAs, 70.5% had an RVOT origin and 29.5% an LVOT origin. HS achieved a correct prediction in 90% patients. This rate dropped to 75% in the subgroup of patients with V3PT OTVA. The correct prediction rate of the other ECG-alone criteria in the whole population ranged from 74 to 82% and from 41 to 76% in V3PT patients, and their Cohen's Kappa coefficient for inter-observer variability assessment ranged from 0.63 to 0.81. R-wave amplitude in V3 was the best ECG parameter for discriminating LVOT origin in V3PT patients. When this parameter was incorporated in the novel Weighted Hybrid Score (WHS) (Figure 1), it correctly classified 99 (94.2%) patients (90% sensitivity, 96% specificity, AUC: 0.97). The WHS discriminatory capacity was maintained in V3PT subgroup, (87% sensitivity, 91% specificity AUC: 0.95). WHS showed a Cohen's kappa coefficient of 0, 82. Finally, WHS was validated in an additional population of 97 patients with OTVAs referred for catheter ablation from three additional external centers; in this testing sample the WHS correctly predicted the SOO in 90% patients and proved to have 89% sensitivity and 90% specificity (AUC: 0.94) for a score ≥2 to predict a LVOT origin. Conclusions: The novel simple-to-use WHS proved to accurately anticipate the PVC's SOO and can be introduced in clinical practice for choosing the first chamber to map.